Persuasão ou manipulação? uma análise do discurso de vendedores a partir da implantação de campanhas de incentivos - Dias, Edson de Paiva (2012)
The central theme of this thesis is the incentive or motivational campaigns and their influence on the construction of salesmen discourses in the retail market of home appliances in the metropolitan region of São Paulo, in 2011. The goal will be to associate the different rules in these campaigns to vendors behavior. And, since their implementation, specifically to better understand the type of approach, aggressiveness and the degree of persuasion or manipulation in the speeches made according to regulations related to them. For this, it was necessary a study in which the definitions of retail activity were clarified, its development over time, the types of stores and their departments, suppliers, forms of assistance and the professionals who work in the area. These were related to a system, called here the point of sale, according to the general theory of systems developed by Avanir Uyemov, and analyzed the strategies with the ultimate goal of "closing the loop" to the consumer. The semiotics of culture proposed by Iuri Lotman, allowed a better understanding of attitudes and reactions observed in the personal relationships established between consumers and sellers, since we have the ability to store information, updated and enriched by experiences that are transmitted through our culture and memory. The foundations of semiotic discourse, written by Mikhail Bakhtin, also contributed to the interpretation of these speeches, formed by taking into consideration the other, as we see on our own self, or a mirror that only provides the material for self-objectification. These theories, along with other authors, allowed a thoughtful analysis about the different variables about the studied problem: the effectiveness or not of the most striking features of language and their consequences to persuade or manipulate consumers to buy specific products and brands. A few researchers have addressed this type of analysis, given the difficulty of treating this subject with stakeholders and obtain materials where these actions are explained, for they are considered "secretive" or strategic. This explains the limited literature on the subject and at the same time motivates us to write a detailed study: may such actions affect manufacturers that do not conform to these strategies? How to win the loyalty of sellers? Does the vicious circle in which these actions operate imply undesirable attitudes? These factors and the excessive interference that these actions cause in the discourses and the ways these vendors use to assist their clients are the concerns of this work